RENAISSANCE ARCHITECTURE (Ta'limning zamonaviy transformatsiyasi, 2024)
Since the 15th century, the socio-economic development of European countries has accelerated. Especially in cities, handicrafts develop and various production enterprises are established. Trade will develop and international trade relations will be established through the seas.